2020
DOI: 10.1152/advan.00030.2019
|View full text |Cite
|
Sign up to set email alerts
|

Using lectures to identify student misconceptions: a study on the paradoxical effects of hyperkalemia on vascular smooth muscle

Abstract: Medical students have difficulty understanding the mechanisms underlying hyperkalemia-mediated local control of blood flow. Such control mechanisms are crucial in the brain, kidney, and skeletal muscle vasculature. We aimed to identify medical students’ misconceptions via assessment of students’ in-class knowledge and, subsequently, improve future teaching of this concept. In-class polling was performed with the TurningPoint clicker response system ( n = 860) to gauge students’ understanding of three physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In a study on causes of worsening acne vulgaris, it was also shown that intuitive concepts common in the general population were still highly prevalent among medical students in their final year of study [ 30 ]. The consistent percentage per semester of intuitive concept selection for internal medicine topics in our study confirmed studies in medical physiology that existing intuitive concepts appeared to have little to no ability to be overcome by previous teaching methods [ 24 ], [ 31 ]. Another study of biomedical science students, using a multilayered approach to study intuitive concepts in cardiovascular physiology, could demonstrate that in nearly one-third of the cases the selection of the intuitive concept was paired with high confidence of having answered the question correctly [ 32 ].…”
Section: Discussionsupporting
confidence: 82%
“…In a study on causes of worsening acne vulgaris, it was also shown that intuitive concepts common in the general population were still highly prevalent among medical students in their final year of study [ 30 ]. The consistent percentage per semester of intuitive concept selection for internal medicine topics in our study confirmed studies in medical physiology that existing intuitive concepts appeared to have little to no ability to be overcome by previous teaching methods [ 24 ], [ 31 ]. Another study of biomedical science students, using a multilayered approach to study intuitive concepts in cardiovascular physiology, could demonstrate that in nearly one-third of the cases the selection of the intuitive concept was paired with high confidence of having answered the question correctly [ 32 ].…”
Section: Discussionsupporting
confidence: 82%
“…Similar findings were reported in previous studies. Following these findings, Bordes et al utilized the SRS to assess students' in-class knowledge by using in-class polling to gauge students' understanding of the key lecture concepts [31]. He concluded that the SRS served as a potential teaching tool to identify student misconceptions and improve student learning outcomes [31].…”
Section: Discussionmentioning
confidence: 99%
“…Following these findings, Bordes et al utilized the SRS to assess students' in-class knowledge by using in-class polling to gauge students' understanding of the key lecture concepts [31]. He concluded that the SRS served as a potential teaching tool to identify student misconceptions and improve student learning outcomes [31]. Li reported that the use of SRS also benefits the lecturer as the teaching evaluation of the lecturer was significantly better for the SRS group [3,4].…”
Section: Discussionmentioning
confidence: 99%